Flames over Baler the story of the siege of Baler, reconstructed from original documentary sources - Madrid, Carlos; Angara, Edgardo J. (Quezon City University of the Philippines Press, 2012)
The Siege of Baler has been a very well-known episode in the Philippines, particularly in connection with the Philippine-Spanish Friendship Day and the 2008 remarkable movie on the siege. In the past, only a handful of local publications discussed it or briefly described what had happened in Baler between 1897 and 1899. Using a deep knowledge of archival sources both in the Philippines and Spain, this reconstruction of the siege brings up the specific details of the complex process of estrangement between the besieged and the besiegers, and the extraordinary dedication and courage that both Filipinos and Spaniards demonstrated to achieve victory, providing a case study for knowledge of the military strategies used at the end of the nineteenth century and the role of image and perceptions in conflict resolution. Moreover, the reconstruction leaves a clearer perception of the astonishing challenges confronted by the men and women who were immersed in the revolutionary process.
1. The Baler region -- 2. First engagements : September 1897-January 1898 -- 3. The Biak na Bato interlude : January-June 1898 -- 4. The plaza as battlefield : June-September 1898 -- 5. Flames over Baler : September-December 1898 -- 6. Out of the loop : December 1898-February 1899 -- 7. Distrust and confusion : February 1899 -- 8. A quiet interlude : March-April 1899 -- 9. Back to fighting, return to negotiations : April-June 1899 -- 10. Reaching the final decision : June 1899 -- 11. End of a tragic odyssey.
Revision of the author's thesis (doctoral)--Madrid.
Includes bibliographical references and index.
Tac-2945g donated by Dr. Zosimo Lee on April 21, 2016.
Keywords: Baler (Philippines) -- History -- Siege, 1898-1899 -- Sources; Baler (Philippines) -- History -- Sources; Philippines -- History -- Revolution, 1896-1898 -- Sources